Peranan Pendidikan Islam Berbasis Masyarakat (Studi terhadap Kajian Rutin di Masjid Raya Istiqlal Kampung Kalawi Kota Padang) - Muliati, Indah; Jamri, Jamri; Noviyenti, Noviyenti (AS-SABIQUN, 2023)
The research is motivated by the problem of moral decadence so that it requires community involvement in education management. This research aims to describe the role of community-based Islamic education in routine studies conducted at the Istiqlal Grand Mosque, Kampung Kalawi. The method used in this research is qualitative. Research data was obtained from primary and secondary sources, namely the chairman, administrators and congregation of the Istiqlal Grand Mosque, Kampung Kalawi. The data collection techniques used are interviews and observation, while the data analysis techniques used are data reduction, data presentation and conclusions. The results of this research show that the routine study activities carried out by the Istiqlal Kampung Kalawi Grand Mosque are numerous in detail: 1) every day after morning prayers, the speakers are from competent community members, 2) every Saturday after morning prayers, the speakers are from outside experts. in the field he studies, with predetermined studies (beliefs, hadith, tafsir and fiqh, 3) every Wednesday after sunset, the speakers are people who are competent in the theme he studies, 4) every Friday after evening prayer, discusses and practices reading the Koran community, the speakers are from outside experts in the field of the Koran. Three roles of community-based Islamic education were found in routine studies at the Istiqlal Grand Mosque in Kalawi Village, namely: strengthening the faith, improving the community's reading of the Koran, and strengthening the Islamic brotherhood.